2013
DOI: 10.3109/10826084.2013.853797
|View full text |Cite
|
Sign up to set email alerts
|

Desired Social Distance From People Who Have Hepatitis C Virus: An Exploration Among Staff in Health Care, Dentistry, Drug Treatment, and Tattoo/Body Piercing

Abstract: Staff who work in facilities such as health care, dentistry, drug treatment, and tattoo/body piercing are likely to encounter persons with hepatitis C virus (HCV) and be privy to their HCV status. The purpose of this paper is to assess staff comfort with varying levels of intimacy (i.e., social distance) with people who have HCV. We examine how previous contact with persons with HCV and knowledge of HCV including HCV specific training affect desire for social distance. Data are from a 2007 sample of 82 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In contrast, however, Dillon and Allwright () found that PCOs who had received BBV training did not have an increased knowledge of their transmission routes or any reduction in anxiety regarding personal risks. Similarly, Suarez and Redmond () observed that HCV knowledge and awareness training did not alter the social distance – a measure of prejudicial attitudes – sought from infected individuals by healthcare staff, drug treatment workers, tattooists and body piercers. Lloyd et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, however, Dillon and Allwright () found that PCOs who had received BBV training did not have an increased knowledge of their transmission routes or any reduction in anxiety regarding personal risks. Similarly, Suarez and Redmond () observed that HCV knowledge and awareness training did not alter the social distance – a measure of prejudicial attitudes – sought from infected individuals by healthcare staff, drug treatment workers, tattooists and body piercers. Lloyd et al .…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, however, Dillon and Allwright (2005) found that PCOs who had received BBV training did not have an increased knowledge of their transmission routes or any reduction in anxiety regarding personal risks. Similarly, Suarez and Redmond (2014) observed that HCV knowledge and awareness training did not alter the social distancea measure of prejudicial attitudessought from infected individuals by healthcare staff, drug treatment workers, tattooists and body piercers. Lloyd et al (2013) found that a lack of HCV-related knowledge among prison staff constituted a barrier to HCV testing and treatment uptake, and so the universal insufficiency of HCV knowledge revealed among the PCOs interviewed in this study will be an important element to address.…”
Section: Educationmentioning
confidence: 92%